2019
DOI: 10.1002/ceat.201800765
|View full text |Cite
|
Sign up to set email alerts
|

Study on Soybean Oil Plant Wastewater Treatment Using the Electro‐Fenton Technique

Abstract: Due to its low viscosity, soybean oil is commonly used as edible oil. Its production is accompanied by a large amount of wastewater containing hazardous materials like phenolic compounds. In this study, the electro‐Fenton process with response surface methodology was applied for oil removal from wastewater of soybean oil plants. Five independent variables, including reaction time, pH, current density, molar ratio of H2O2 to Fe2+, and volume fraction of H2O2 to wastewater, were investigated for their effects on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…Also, unwanted liquid, solid and gaseous wastes are generated together with the desired products (edible oils). 1 Edible oil refinery wastewater is generated from the degumming, deacidification, and deodorisation and neutralisation processes. 2 The indiscriminate disposal of this waste and wastewater results in severe environmental pollution and health hazards.…”
Section: Introductionmentioning
confidence: 99%
“…Also, unwanted liquid, solid and gaseous wastes are generated together with the desired products (edible oils). 1 Edible oil refinery wastewater is generated from the degumming, deacidification, and deodorisation and neutralisation processes. 2 The indiscriminate disposal of this waste and wastewater results in severe environmental pollution and health hazards.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, a combination of physical, chemical, and biological treatment units is typically required. For instant, it is typically required to employ the chemical treatment method as a pretreatment step prior to the biological wastewater treatment system [2][3]. Reddy et al [2] suggested removing FOG before other treatments.…”
mentioning
confidence: 99%